Between mathematical formalism, normative choice rules, and the behavioral sciences: The emergence of rational choice theories in the late 1940s and early 1950s - Catherine Herfeld (Duke University, Center for the History of Political Economy (CHOPE), 2017)
This paper discusses why mathematical economists of the early Cold War period favored formal-axiomatic over behavioral choice theories. One reason was that formal-axiomatic theories allowed mathematical economists to improve the conceptual and theoretical foundations of economics and thereby to increase its scientific status. Furthermore, the separation between mathematical economics and other behavioral sciences was not as clear-cut as often argued. While economists did not modify their behavioral assumptions, some acknowledged the empirical shortcomings of their models. The paper reveals the multifaceted nature of rational choice theories reflected in the changing interpretations and roles of the theories in those early years.
Keywords: B00; B2; B3; B4; 330; history of rational choice theory; Cowles Commission; normative turn